USE OF ANTIBIOTICS AT THE SURGERY DEPARTMENT OF TRA VINH GENERAL HOSPITAL IN 2017 AND SOME FACTORS AFFECTING (Vietnam Journal of Community Medicine, 2022)
Objectives: A study to assess the current situation of antibiotic use in surgery and its influencingfactors at the Department of Surgery, Tra Vinh Provincial General Hospital.The results: The overall rate of patients using antibiotics was 44, 78%, and on surgery was 100%.Several factors affect antibiotic use: age, gender, and use of medical insurance. In addition, the studyidentified some factors that determine the use of antibiotics: Treatment regimens, decision to chooseantibiotics for patients and doctors, antibiotic supply of the Faculty of Pharmacy, and informationon drug updates.Recommendations: Develop regulations on drug use and drug combination; clarify the criteria fordrug use, develop quality standards and provide indicators to assess drug resistance. Improve themanagement of drug use by doctors and clinical departments.
Keywords: Antibiotic use, factor influence.